Band gaps induced by vacuum photons in closed semiconductor cavities - Kibis, O. V. (2015)
We consider theoretically a closed (zero-dimensional) semiconductor microcavity where a confined vacuum photonic mode is coupled to electrons in the valence band of the semiconductor. It is shown that vacuum-induced virtual electron transitions between valence and conduction bands result in renormalization of electron energy spectrum. As a consequence, vacuum-induced band gaps appear within the valence band. Calculated values of the band gaps are of sub-meV scale, which makes this QED effect measurable in state-of-the-art experiments.